Cost‐effectiveness of treatments for superficial venous reflux in patients with chronic venous ulceration. Issue 4 (10th May 2018) - Epstein, D.; Gohel, M.; Heatley, F.; Davies, A. H.
Abstract : Background: Venous leg ulcers impair quality of life significantly, with substantial costs to health services. The aim of this study was to estimate the cost‐effectiveness of interventional procedures alongside compression therapy versus compression therapy alone for the treatment of chronic venous leg ulceration. Methods: A Markov decision analytical model was developed. The main outcome measures were quality‐adjusted life‐years (QALYs) and lifetime costs per patient, from the perspective of the UK National Health Service at 2015 prices. Resource use included the initial procedures, compression therapy, primary care and outpatient consultations. The interventional procedures included superficial venous surgery, endothermal ablation and ultrasound‐guided foam sclerotherapy (UGFS). The study population was patients with a chronic venous ulcer who were eligible for either compression therapy or an interventional procedure. Data were obtained from systematic review and meta‐analysis of RCTs. Results: Surgery gained 0·112 (95 per cent c.i. −0·011 to 0·213) QALYs compared with compression therapy alone, with a difference in lifetime costs of €−1330 (−3570 to 1262). Given the expected savings in community care, the procedure would pay for itself within 4 years. There was insufficient evidence regarding endothermal ablation and UGFS to draw conclusions. Discussion: This modelling study found surgery to be more effective and less costly than compression therapy alone. Further RCT evidence is required for both endothermal ablation and UGFS. Abstract : What is already known about this subject: Venous leg ulcers cause significant morbidity and impaired quality of life, with substantial cost to health services. Mauck et al., in a systematic review of RCTs, found superficial venous surgery alongside compression therapy was more effective in preventing recurrence than compression therapy alone. Until now, there have been no economic analyses of interventional procedures for venous leg ulcers. What this study adds: This is the first cost‐effectiveness analysis of interventional procedures for venous leg ulcers. The study found that surgery is both more effective and less costly than compression therapy alone. There was insufficient evidence to draw definitive conclusions about whether other interventional procedures such as endothermal ablation are likely to be cost‐effective. Surgery cost‐effective for ulcers